2003
DOI: 10.1213/01.ane.0000056921.15974.ec
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of KCNK5 or Kir3.2 Potassium Channels in Mice Does Not Change Minimum Alveolar Anesthetic Concentration

Abstract: Mice harboring mutations in either of two different potassium channels have minimum alveolar anesthetic concentration (MAC) values that do not differ from MAC values found in control mice. Such findings do not support the notion that these potassium channels mediate the capacity of inhaled anesthetics to produce immobility in the face of noxious stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Information on the likely relevance of two-pore-domain channels to general anesthesia may come from genetically modified animals in which certain members of the superfamily are either modified or excluded. A recent study (Gerstin et al, 2003) on such a knock-out animal has used this approach and concluded that TASK-2 (KCNK5) channels are unlikely to be important for general anesthesia. Because the anatomical distribution and anesthetic sensitivities of two-pore-domain channels vary so greatly, the lack of importance of one member of the family cannot easily be extrapolated to other members, and the role of the channels we have studied (TREK-1 and TASK-3) in general anesthesia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the likely relevance of two-pore-domain channels to general anesthesia may come from genetically modified animals in which certain members of the superfamily are either modified or excluded. A recent study (Gerstin et al, 2003) on such a knock-out animal has used this approach and concluded that TASK-2 (KCNK5) channels are unlikely to be important for general anesthesia. Because the anatomical distribution and anesthetic sensitivities of two-pore-domain channels vary so greatly, the lack of importance of one member of the family cannot easily be extrapolated to other members, and the role of the channels we have studied (TREK-1 and TASK-3) in general anesthesia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite activation of TASK-2 by volatile anesthetics there was little evidence supporting a role for TASK-2 in mediating anesthesia. TASK-2 expression in the spinal cord suggested that its activation may significantly affect motor and sensory pathways during anesthesia however sensitivity to volatile anesthetics was not affected in TASK-2 knockout mice [57]. TASK-2 channels were also inhibited by local anesthetics and, like many other K2P channels, were most sensitive to bupivacaine [107] whereas TALK-2 was relatively insensitive [41].…”
Section: Talk Pharmacological Characteristicsmentioning
confidence: 99%
“…Effects of different inhaled anesthetics on ion channel (e.g., K ? ) [12,13] as well as in different receptors [14] have also been reported. In these biophysical studies, the concentrations of halothane, isoflurane, and sevoflurane were determined by gas chromatography [10].…”
Section: Anesthetic and Protein Interactionmentioning
confidence: 82%